EVALUASI PELAKSANAAN PROGRAM LANSIA SMART DI WILAYAH KERJA PUSKESMAS SUNGAI SALAK KABUPATEN INDRAGIRI HILIR TAHUN 2023 - Silaban, Helen Ernawati; Afandi, Dedi; Nurhapipa, Nurhapipa; Dewi, Oktavia; Marlina, Hastuti (Ensiklopedia of Journal, 2024)
The development of elderly health programs is aimed at achieving Healthy, Independent, Active and Productive (SMART) Elderly, so as to maintain their mental, psychosocial and spiritual health. The lowest elderly data in utilizing Elderly Health Services in the working area of the Indragiri Hilir Regency Health Center is the Sungai Salak Health Center with 96 elderly (17.329%). The purpose of the study is to analyze policies, human resources, facilities, and financing for the implementation of the SMART Elderly Program in the Sungai Salak Health Center Working Area. This type of research is qualitative, descriptive, with a case study design. The research location is in the Working Area of the Sungai Salak Health Center, Indragiri Hilir Regency. The research period is January to August 2023. The informants consisted of 5 main informants (Elderly Program Holders at the Community Health Center and 4 Pustu Responsible Persons), and 4 supporting informants (Head of Puskesmas, Elderly Program Holders at the Health Office and 2 Elderly people). Data collection was conducted through in-depth interviews, observations and document review. Data validity is done by triangulation of sources, methods, and data. The result of this study is that the SMART Elderly Program has not been running, which is running only for the Healthy Elderly and even then only the activities of the Elderly Posyandu. It is expected that the Community Health Center coordinates with Cross Sectors to make activities related to the Elderly Healthy, Independent, Active and Productive.Keywords: Integrated service post for the Elderly, Sungai Salak community health center, and SMART Elderly Program